Effectiveness of selenium supplementation in children with autoimmune thyroiditis: A systematic review and meta-analysis - Yuni Hisbiyah, - (Universidad Tecnica de Manabi, 2022)
ABSTRACT Deficiencies of Selenium (Se) is correlated with the risk and onset of autoimmune thyroid disease (AITD). The aim of this study was to determine the association between Se supplementation and AITD. Methods: Electronic data searches of 4 databases were performed. We assessed the included studies using PRISMA for protocol assurance. Five studies met our inclusion criteria and were analyzed. The predictor covariate in the present study was Se administration. The outcome measures were levels of thyroid peroxidase antibodies (TPO-Ab), thyroglobulin antibody (Tg-Ab), free thyroxine (fT4), and thyroid volume. Results: Of the five studies that met the inclusion criteria, one randomized controlled trial (RCT) was included in the qualitative review, whereas four quasi-experimental studies were included in the meta-analysis. The results showed that Se supplementation significantly reduced TPO-Ab levels (MD 90.85; 95% CI 61.71–120.00; p<0.00001) and fT4 levels (MD 1.52; 95% CI, 0.55–2.50; p=0.002), while the RCT showed that Se supplementation significantly reduced Tg-Ab levels. Conclusions: Se supplementation significantly reduces TPO-Ab and fT4 levels in children and adolescents with AITD. The limited number of studies and population sizes emergence of further studies especially RCTS are needed to make a better meta-analysis